The Relationship Between Blue Light Exposure from Digital Devices and the Acceleration of Premature Aging in Young Adults - Lassie, Naima (Oshada, 2025)
The use of digital devices among young adults has increased substantially, leading to higher exposure to blue light in everyday life. Blue light exposure has been associated with oxidative stress and cellular dysfunction of the skin, which are closely related to the aging process. This study aims to examine the relationship between blue light exposure from digital devices and accelerated premature aging among young adults. A quantitative explanatory approach with a cross-sectional design was employed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The sample consisted of 210 young adults aged 18–35 years who actively use digital devices. The results indicate that blue light exposure has a positive and significant effect on premature aging. These findings confirm that daily digital exposure represents a lifestyle-related risk factor contributing to accelerated skin aging. This study provides empirical evidence to support preventive strategies for skin health in the digital era.